The Disease Burden, Risk Factors and Predictive Analysis of Early-onset Colorectal Cancer of Different Genders between China and the World from 1990 to 2021 - LIAO Xingyu, TIAN Siyu, CHEN Min (Zhongguo quanke yixue)
Background In recent years, the incidence of colorectal cancer has been on the rise in low- and middle-income countries. Early-onset colorectal cancer (EOCRC), defined as colorectal cancer occurring in patients under 50 years of age, continues to see an increasing incidence. However, there is currently a lack of relevant epidemiological trends, which may hinder precise prevention, control strategies, and resource allocation for EOCRC. Objective To analyze the trends in the disease burden of EOCRC and the major risk factors for EOCRC in China and Global across different genders from 1990 to 2021 and predict the incidence and mortality rates of EOCRC for different genders in China and global from 2022 to 2046. Methods The incidence, mortality and disability adjusted life year (DALY) rate of colorectal cancer diagnosed between the ages of 14 and 49 in China and Global from 1990 to 2021 were collected using the Global Burden of Disease Database 2021. Age-standardized incidence rates (ASIR), age-standardized mortality rates (ASMR), and age-standardized disability-adjusted life years (ASDR) were utilized to analyze the disease burden of EOCRC and its major risk factors by gender in China and global. The Joinpoint model was used to calculate the annual percentage change (APC) and the average annual percentage change (AAPC) to reflect the trends in disease burden changes. Furthermore, the Bayesian age-period-cohort (BAPC) model was used to predict the incidence and mortality rates of EOCRC for different genders in China and globally from 2022 to 2046. Results In 2021, the ASIR, ASMR, ASDR for Chinese males in EOCRC were 13.39/100 000, 4.26/100 000, 220.59/100 000, the ASIR, ASMR, ASDR for Chinese females in EOCRC in were 5.75/100 000, 1.68/100 000, 87.29/100 000. In 2021, the ASIR, ASMR, ASDR for global males in EOCRC were 6.11/100 000, 2.29/100 000, and 115.58/100 000, the ASIR, ASMR, ASDR for Chinese females in EOCRC were 4.17/100 000, 1.57/100 000, and 79.49/100 000. The AAPC for ASIR of males in China and global was 2.09% (95%CI=1.76%-2.43%) and 0.73% (95%CI=0.61%-0.84%), while for females in China, it was 0.31% (95%CI=0.04%-0.59%), all indicating an upward trend (P<0.05). The AAPC for the ASMR for males in China and global was -0.28% (95%CI=-0.51% to -0.05%) and -0.54% (95%CI=-0.68% to -0.40%), the AAPC was -2.22% (95%CI=-2.47% to -1.97%) in Chinese female and -1.25% (95%CI=-1.37% to -1.13%) in global female, all indicating a downward trend (P<0.05). The trend of ASIR trend for global females exhibited fluctuations, with AAPC of -0.09% (95%CI=-0.22% to 0.04%) (P>0.05). The trend of ASDR for Chinese male showed an inverted "V" shape, with AAPC of -0.20% (95%CI=-0.45% to 0.04%) (P>0.05). By 2046, the predicted ASIR and ASMR for Chinese male are expected to be 28.46/100 000 and 4.80/100 000. For females in China, these rates are projected to be 7.41/100 000 and 1.23/100 000. Globally, the ASIR and ASMR for males are forecasted to be 5.90/100 000 and 1.62/100 000, while for females, the rates are expected to be 3.06/100 000 and 1.05/100 000. Conclusion The disease burden of EOCRC in both males and females in China is severe and exceeds the global average, exhibiting significant gender disparities. There is a need to deepen the focus on the gender disparities associated with EOCRC and to implement targeted prevention and control measures. Additionally, drawing on global prevention and treatment experiences can provide a valuable reference for policy formulation.